1992
DOI: 10.3109/10731199209117860
|View full text |Cite
|
Sign up to set email alerts
|

On the Perfluorocarbon Emulsions of Second Generation

Abstract: For formulation of perfluorocarbon-emulsions (PFC-emulsions) of second generation new perfluorocarbons (F-dimorpholines, F-dipiperidines and F-cyclohexylmorpholine) were synthesized, acting both as oxygen carriers and as interfacial active compounds (IFACs). The stabilizing effect of these IFACs is interpreted and a new theory is introduced. Also new classes of fluorosurfactants were synthesized and tested for biocompatibility. In PFC mixtures compounds of the type RFRH (RF = CmF2m + 1, RH = CnH2n + 1) are act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Mass spectrometric studies on a series of partially fluorinated alkanes have confirmed their great stability [2]. The main applications for triblock and diblock semifluorinated n-alkanes ranging from biomedical field, as oxygen-carrying agents for blood substitutes [3][4][5][6][7][8], ophthalmology applications [9][10][11][12][13], perfluorocarbons emulsion stabilization [14,15], to applications as solid lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometric studies on a series of partially fluorinated alkanes have confirmed their great stability [2]. The main applications for triblock and diblock semifluorinated n-alkanes ranging from biomedical field, as oxygen-carrying agents for blood substitutes [3][4][5][6][7][8], ophthalmology applications [9][10][11][12][13], perfluorocarbons emulsion stabilization [14,15], to applications as solid lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…19 Synthetic fluorosurfactants have been shown to nearly eliminate PFC/saline interfacial tension. 145 As such, the potential for LAV techniques to minimize pulmonary barotrauma is differ-entiated by the degree to which interfacial tensions are reduced.…”
Section: Biophysical Basis For Physiologic Differences Between Lav Tementioning
confidence: 99%
“…15-17 'Custom-builtsurfactants are currently being designed with fluoroalkylated chain backbones to give greater fluorocarbon solubility and polar 'head' regions for the aqueous phase based on amino acids, sugars and other biological constituents. 18 In the future, there will be the possibility of modifying the biological response to the emulsion by adapting its emulsifier characteristics. 19,20 Newer fluorocarbons have also incorporated bromide moieties into the structure.…”
Section: Introductionmentioning
confidence: 99%